Economic freedom and academic freedom across nations - Niclas Berggren; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2024)
Academic freedom is a cornerstone of modern academic life. It is not only implied by basic liberal principles but also contributes to scientific progress and economic growth. It is therefore important to better understand what affects how free scholarly pursuits are, and to that end, we ask whether economic freedom can help explain variation in academic freedom across countries. In our case, relating the Economic Freedom of the World index and its five areas to V-Dem's index of academic freedom and its five areas reveals that the rule of law is positively and robustly related to academic freedom in all its forms. This suggests that the rule of law, in its general and broad sense, can arguably serve as a guarantor of academic freedom. Where the rule of law is weakened, academic freedom can be at risk. There are some indications that regulatory freedom is similarly related to academic freedom, but less robustly so, maybe indicating that interventionism in one policy area (economics) can breed interventionism in another (academia).
Keywords: D72; I23; K40; 330; Freedom; markets; rule of law; legal system; academic freedom